Contrast-Enhanced Endoscopic Ultrasonography for Pancreatic Tumors - Yamashita, Yasunobu (Biomed Res Int, 2015)
Objectives. To investigate the usefulness of contrast-enhanced endoscopic ultrasonography (CE-EUS) for histological differentiation of pancreatic tumors. Methods. CE-EUS was performed for consecutive patients having a pancreatic solid lesion, and tumors were classified into three vascular patterns (hypervascular, isovascular, and hypovascular) at two time phases (early-phase and late-phase). Correlation between vascular patterns and histopathology of resected pancreatic cancer (PC) tissues was ascertained. Results. The final diagnoses of 147 examined tumors were PC (n = 109), inflammatory mass (n = 11), autoimmune pancreatitis (n = 9), neuroendocrine tumor (n = 8), and others (n = 10). In late-phase images, 104 of 109 PCs had the hypovascular pattern, for a diagnostic sensitivity and specificity of 94% and 71%, respectively. Of 28 resected PCs, 10 had isovascular, and 18 hypovascular, patterns on the early-phase image. Early-phase isovascular PCs were more likely to be differentiated than were early-phase hypovascular PCs (6 well and 4 moderately differentiated versus 3 well, 14 moderately, and 1 poorly differentiated, P = 0.028). Immunostaining revealed that hypovascular areas of early-phase images reflected heterogeneous tumor cells with fibrous tissue, necrosis, and few vessels. Conclusion. CE-EUS could be useful for distinguishing PC from other solid pancreatic lesions and for histological differentiation of PCs.